Brain-wide multi-fiber recording of neuronal activity in freely moving mice - Bing Dai; Zhichao Guo; Dayu Lin (STAR Protocols, 2024)
Summary: While brain regions function in coordination to mediate diverse behaviors, techniques allowing simultaneous monitoring of many deep brain regions remain limited. Here, we present a multi-fiber recording protocol that enables simultaneous recording of fluorescence signals from multiple brain regions in freely behaving mice. We describe steps for assembling a multi-fiber array and patch cord, implantation, and recording. We then detail procedures for data extraction and visualization. This protocol enables a comprehensive view of the neural activity at the network level.For complete details on the use and execution of this protocol, please refer to Guo et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.